2023
DOI: 10.3390/cimb45020096
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Aloe saponaria against Ulcerative Colitis Induced by Dextran Sulfate Sodium

Abstract: Aloe vera (A. vera) has been studied as a treatment option for ulcerative colitis (UC), but there is a lack of scientific evidence showing whether treatment with Aloe saponaria (A. saponaria) can also be beneficial. To investigate the therapeutic potential of A. saponaria as a treatment for UC, clinical symptoms, histopathological characteristics of the colon, inflammatory response, and toxicity were analyzed in dextran sulfate sodium (DSS)-induced UC mice after administration of aqueous extracts of A. saponar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Therefore, aloe-derived nanovesicles can be effective prophylactic and therapeutic agents for IBD treatment. A study is now under way to identify components and ingredients 57,58 that contribute to leveraging therapeutic potentials of aloe-derived nanovesicles in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, aloe-derived nanovesicles can be effective prophylactic and therapeutic agents for IBD treatment. A study is now under way to identify components and ingredients 57,58 that contribute to leveraging therapeutic potentials of aloe-derived nanovesicles in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Kweon et al revealed that aquatic Aloe saponaria (AAS) extract displays significant antioxidant activities and can greatly regulate the inflammatory response. In dextran sulfate sodium (DSS)-induced ulcerative colitis mice, AAS extract significantly restored the phosphatidylinositol-3-kinase/serine-threonine protein kinase (PI3K/Akt) and phosphatidylinositol-3-kinase/serine-threonine protein kinase/Akt (PI3K/Akt) signaling pathways [5].…”
mentioning
confidence: 99%